Optimalisasi Tingkat Kevakuman Pada Fresh Water Generator di MV. Glovis Daylight - Irma Fasadal Walid Zumrotun; Pambudi Widiatmaka (Politeknik Ilmu Pelayaran Semarang, 2020)
A freshwater generator is one of the auxiliary machines onboard which functions to convert seawater into freshwater by distilling it in a vacuum. Fresh water on the ship is very important for crew accommodation and also for the smooth work of machinery on ships that use freshwater for cooling media or for other purposes. The working principle of a freshwater generator is to separate the salt content in seawater by evaporating it in a vacuum so that the boiling point decreases and the water can evaporate below a temperature of 100oC. Problems and disturbances in the freshwater generator will affect the amount of freshwater production, therefore the condition of the auxiliary machine must be maintained. In this study, the authors used the fishbone analysis method to describe the factors that caused the vacuum that was not optimal and to find out the causes, impacts, and efforts made to overcome these problems. Based on the results of research that the author has done in MV. During the practice, Glovis Daylight concluded that the inadequate vacuum in the freshwater generator was caused by low ejector pump pressure, broken mechanical seal on the ejector pump, dirty strainer, and crust on the condenser and evaporator plates. The resulting impact is that the resulting freshwater production will decrease. Efforts to overcome this require routine maintenance according to the manual book, replacement of mechanical seals, cleaning strainer, and descaling of the condenser and evaporator plates.